The impact of Artificial Intelligence on human rights: ethical dimensions - Yanenko, Sofia; Duzhyk, Nataliia (My University, 2023)
Commonly raised problems related to the use of AI are discussed. Among them are employment discrimination, privacy violation, misinformation, and automated decision-making. The findings demonstrate the effective ways of enhancing the quality of AI-enabled products. Обговорюються поширені проблеми, пов’язані з використанням ШІ. Серед них дискримінація при працевлаштуванні, порушення конфіденційності, дезінформація та автоматизоване прийняття рішень. Результати дослідження демонструють ефективні способи покращення якості продуктів із штучним інтелектом.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; biased design; misinformation; product testing; violation of human rights; упереджений дизайн; дезінформація; тестування продукту; порушення прав людини